Key components of mechanical work predict outcomes in robotic stroke therapy. - Wright, Zachary A.; Majeed, Yazan A.; Patton, James L.; Huang, Felix C. (Tufts University. Tisch Library., 2020)
Keywords: Stroke, Robotic therapy, Upper limb, Energetics, Neurorehabilitation, Outcomes.; Springer Open.